The Study of Depression and Loneliness among Elderly Women - Lukman@Zawawi, Mohamad; Nurun Saadah, S.; Syafiq, M.S (2018)
Depression and loneliness among elderly women who live in the home care institution have become a world phenomenon in developed countries. These mental health diseases are most common factors that lead to the deficiency of daily routine activities such as socializing and many more. However, in third world countries or developing countries, depression and loneliness are being studied differently and no legit findings of the relationship between these two variables. Hence, this research is to identify the relationship between depression and loneliness among elderly women in-home care institution. Method of this research used quantitatively. The respondent in the institution is 180 people. This research used University of California Los Angeles Loneliness Scale (UCLA LS) and Patient Health Questionnaire 9 (PHQ-9). This research used the Pearson Correlation Coefficient to identify the relationship between depression and loneliness. The result showed the relationship between depression and loneliness among elderly women in an institution is r=0.828 and it is significance in p>0.003. As a conclusion, the depression and loneliness among elderly women in the home care institution is significance and it brings to the new dimension of knowledge and practicality about these mental health diseases especially in third and developing countries.